Strategi Pemasaran Produk Tempe Kita Bandung Melalui Analisis SWOT dan Matriks IE - Mohamad Lukman Hakim; Ida Farida Oesman; Rama Chandra Jaya; Ridlwan Muttaqin (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
Tempe Kita Bandung, which has been operating since 1988, faces challenges of fluctuating revenue and intense price competition, as well as limited distribution that is still focused on traditional markets, making it difficult to reach a wider and more modern market segment. This study aims to analyze internal and external factors, determine the strategic position of the business, and formulate the most effective marketing strategy through a SWOT Analysis approach and an Internal-External (IE) Matrix. This descriptive study uses a mixed approach (quantitative and qualitative). Primary data were obtained through in-depth interviews with the owner or manager and questionnaires to key informants, while secondary data were obtained from internal company documents. The data analysis techniques used were the IFAS and EFAS Matrices to obtain weighted scores, which were then plotted on the IE Matrix to determine strategic position, and further processed through the SWOT Matrix to generate alternative strategies. The expected analysis results indicate that Tempe Kita Bandung has strengths in product experience and quality, but is weak in digital marketing adaptation. The strategic position of the business is estimated to be in the quadrant that requires a Hold and Maintain strategy. Therefore, the recommended marketing strategies are Weakness-Opportunity (WO) and Strength-Threat (ST) strategies, which are implemented through digital market penetration to address distribution weaknesses and premium product differentiation to counter the threat of low-price competition. This strategy is expected to increase business competitiveness and expand market reach.